2021
DOI: 10.1590/s1980-220x2020003203747
|View full text |Cite
|
Sign up to set email alerts
|

Índices de gravidade em vítimas de trauma contuso na terapia intensiva: capacidade preditiva de mortalidade

Abstract: RESUMO Objetivo: Identificar a capacidade preditiva de mortalidade dos índices Revised Trauma Score, Rapid Emergency Medicine Score, modified Rapid Emergency Medicine Score e Simplified Acute Physiology Score III em vítimas de trauma contuso internadas em unidade de terapia intensiva e comparar seu desempenho. Método: Coorte retrospectiva de pacientes com trauma contuso de uma unidade de terapia intensiva a partir do registro em prontuários. Receiver Operating Characteristic e intervalo de confiança de 95% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Research carried out in Brazil identified that the performance of SAPS III (AUC 0.811), mREMS (AUC 0.802), RTS (AUC 0.747) and Rapid Emergency Medicine Score (REMS) (AUC 0.753) for predicting death in the ICU of surgical patients who suffered blunt trauma was similar and moderate, with no preferential indication of one of these indexes for use in the clinical practice of professionals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research carried out in Brazil identified that the performance of SAPS III (AUC 0.811), mREMS (AUC 0.802), RTS (AUC 0.747) and Rapid Emergency Medicine Score (REMS) (AUC 0.753) for predicting death in the ICU of surgical patients who suffered blunt trauma was similar and moderate, with no preferential indication of one of these indexes for use in the clinical practice of professionals [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the performance of trauma indices for predicting the probability of in-hospital survival or mortality is frequently addressed in different studies [ 5 , 7 , 14 16 ]; however, the analysis of the predictive capacity of these indices for admission and mortality in the ICU is scarce. Results show that the ISS and NISS perform well in identifying severe trauma patients who need intensive care [ 17 , 18 ] and the TRISS and the mREMS are highlighted as predictors of death in the ICU of this population [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, trauma indices have been developed over the years to determine the severity of patients, which assess the severity level of anatomical injuries and/or the physiological conditions of them by using uniform language, making it possible to estimate the survival probability of the trauma patients. These systems have been used to assist in evaluating the care provided and planning emergency care, in addition to enabling documentation of the severity in the description of the epidemiological characteristics of the trauma victims 4,5. In daily practice, trauma nurses continuously plan and make decisions about nursing interventions6 that are influenced by severity of trauma patients.…”
mentioning
confidence: 99%
“…These systems have been used to assist in evaluating the care provided and planning emergency care, in addition to enabling documentation of the severity in the description of the epidemiological characteristics of the trauma victims. 4,5 In daily practice, trauma nurses continuously plan and make decisions about nursing interventions 6 that are influenced by severity of trauma patients. Therefore, the reliability of severity indices is within the scope of interest of the trauma nurses.…”
mentioning
confidence: 99%
“…Esses cinco componentes recebem valores de zero a +4 no cálculo do REMS e a pontuação atribuída à idade varia de zero a seis. A capacidade preditiva de mortalidade desse instrumento tem sido similar a outros índices que estimam a gravidade do trauma de pacientes em unidades de terapia intensiva e na emergência(18) .O REMS foi elaborado mediante regressão logística que analisou diversas características clínicas dos pacientes. Sua composição inclui os preditores independentes para mortalidade identificados em análise multivariada.…”
unclassified